2000
DOI: 10.1037/1076-8998.5.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions to women's social identity: A comparative study of workplace stress experienced by women in three geographic regions.

Abstract: Drawing on social identity theory (P. J. Burke, 1991) and the current status of women and equal opportunity legislation, the authors tested several factors associated with distress in working women in the People's Republic of China (PRC), Hong Kong, and the United States. Women in Hong Kong experienced significantly greater levels of life stress than PRC and U.S. women. Reports of negative attitudes toward women, gender evaluation, and avoidance coping were greater for Hong Kong and PRC women than for U.S. wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…For each condition that they nominated, participants were asked to indicate on a three point scale how much they thought it affected their everyday functioning. A health scale of this nature has previously been used by Steinberg et al (1994) and in a road safety context by Stalvey and Owsley (2000). The selfratings of the extent to which medical conditions affected everyday functioning were summed for each participant to give an index of general health.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…For each condition that they nominated, participants were asked to indicate on a three point scale how much they thought it affected their everyday functioning. A health scale of this nature has previously been used by Steinberg et al (1994) and in a road safety context by Stalvey and Owsley (2000). The selfratings of the extent to which medical conditions affected everyday functioning were summed for each participant to give an index of general health.…”
Section: Apparatusmentioning
confidence: 99%
“…The participants were required to complete a questionnaire on driving habits and attitudes that was based on questionnaires used previously in studies of older drivers (Owsley, Stalvey, Wells, & Sloane, 1999;Stalvey & Owsley, 2000). Included in the questionnaire were items about avoidance of difficult driving situations.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Stalvey and Owsley (2000) found that self-regulation can be missing at least for some sub-groups of older drivers and advocated interventions that promote self-regulation and the use of compensatory strategies as one means to ensure continued and adequate levels of both mobility and safety. A graduated driving reduction program systematically and comprehensively applied by a licensing authority to appropriate drivers only, would comply with this recommendation.…”
Section: Discussion and Recommendationsmentioning
confidence: 98%
“…Gyllensten and Palmer (2005) report that women who are employed in an organisation that practices gender bias culture have lower salaries, less opportunity to promoted, and lower positions as compared to men who have the same educational background and work experience. According to Shaffer et al (2000), women with a college education take home paychecks similar to men with high school education in the United States.…”
Section: Literature Review Gender Bias In the Workplace And Public Rementioning
confidence: 99%